Assessing the health and development of ART-conceived young adults: A study of feasibility, parent recall, and acceptability - Baker HW Gordon; Hammarberg Karin; Fisher Jane RW; McBain John C (BMC, 2008)
Abstract Background Assisted reproductive technologies (ART) to treat infertility have been available for nearly three decades. There have been a number of systematic comparisons of the health and development of ART-conceived with spontaneously-conceived (SC) children. Data are equivocal, some finding no differences and others that there are more health and developmental problems in the ART group. It is agreed that perinatal mortality and morbidity are worse after assisted than spontaneous conception and the impact of the hormonally altered intrauterine environment on puberty and later fertility of offspring are unknown. To date however, there has been no investigation of the health and development of ART-conceived young adults, including from the world's few prospective cohorts of ART conceived children. Obtaining these data requires contact to be made with people at least twenty years after discharge from the treating service. Given the ethical difficulties of approaching families to participate in research up to two decades after cessation of treatment, the aim of this exploratory qualitative investigation was to assess the feasibility and acceptability of approaching mothers treated for infertility prior to 1988, and their recall of the health and development of their ART-conceived young adult children. Methods Mothers treated for infertility at the Royal Women's Hospital Reproductive Biology Unit in Melbourne, Australia prior to 1988 were approached by a senior clinician and invited to participate in individual semi-structured interviews which could include their partners and/or young adult children if they wished. Recruitment continued until theoretic saturation had been reached. Results Ten mothers, two of their husbands and five young adults participated in interviews, and the health and development of 15 ART-conceived young adults were described. The experience of conception, pregnancy, birth and the health and development of the children were recalled vividly and in detail. Families were pleased to have been approached and supported the need for systematic data collection. Mode of conception had been disclosed from childhood to all the offspring. Conclusion With careful and sensitive recruitment strategies it is feasible and acceptable to contact women treated for infertility at least two decades ago and their families, to assess the health and development of ART-conceived young adults.